PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII2 SMP NEGERI 21 PEKANBARU - Puspa Ariani; Atma Murni; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students’ math achievement at class VIII2 SMP Negeri 21 Pekanbaru under the Mastery Minimum Criteria with percentage of 37,5%, there are only 15 students from 40 students who achieve the Basic competence completing mathematical models of the problems associated with systems of linear equations of two variables and their interpretation and then the learning process still teacher center. The research is classroom action research. This research aims to increase learning process and students’ math achievement at class VIII2 SMP Negeri 21 Pekanbaru through the implentation cooperative learning model Two Stay Two Stray. The subject of the research are 24 students from class VIII2 SMP Negeri 21 Pekanbaru consist of 19 male and 21 female students with the heterogenous level. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative descriptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. The results of this research showed an increasing number of students’ math achievement from the basic score with the percentage 37,5% to 52,8% on the first daily test and 62,5% on the second daily test. Based on the result of this research can be concluded that the implementation of Cooperative Learning Type Two Stay Two Stray can improve students’ math achievement at class VIII2 SMP Negeri 21 Pekanbaru in the second semester 2015/2016 academic years.Key Word : Students’ Math Achievement, Cooperative Learning Model Two Stay Two Stray, Classroom Action Research.